Shopee-Pay as an Electronic Transaction Instrument: A Maqāṣid al-Sharīʿah Perspective - Okta Prinoza; Wargo; Zaenal Abidin (Zabags Qu Publish, 2025)
The rapid expansion of financial technology in Indonesia has reshaped everyday transaction patterns, notably through digital wallets and paylater services offered by e-commerce platforms such as Shopee. While these services deliver convenience, efficiency, and broader accessibility, questions remain regarding their alignment with the principles of maqāṣid al-Sharīʿah, particularly the protection of wealth and the prevention of consumer harm. This study analyzes the transaction mechanics of ShopeePay and evaluates their conformity with maqāṣid al-Sharīʿah. Employing a qualitative phenomenological approach, data were collected through in-depth interviews, observation, and documentation, and validated via triangulation. Findings indicate that ShopeePay, as an electronic payment instrument, is perceived as efficient, secure, and supportive of financial inclusion; however, the Shopee PayLater feature introduces ethical concerns due to potential interest-like late fees and heightened risks of consumptive behavior. The study advances the Islamic fintech literature by underscoring the need to integrate maqāṣid al-Sharīʿah into assessments of digital financial services and offers practical implications for regulators and industry practitioners to design Sharia-compliant contractual models and strengthen ethics-driven digital financial literacy.